Preparation of photo curable highly hydrophobic coatings using a modified castor oil derivative as a sol-gel component - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE SA, 2011)
Modification and use of natural products have gained a lot of interest in recent years due to their environmental friendliness and their availability from different sources. In this study castor oil based photo curable highly hydrophobic coatings were prepared and characterized. Castor oil (CO) was first modified with 3-isocyanato propyl triethoxy silane and then it was hydrolyzed prior to the coating preparation. The resulting precursor was mixed with norbornyl acrylate, hexane diol diacrylate and hydrophobic coatings were prepared with the aid of fluorinated and nonfluorinated alkoxy silane coupling agents. The addition of fluorine showed a significant impact on the properties of the coatings. As the fluorine content was increased in the formulations, flame retardancy and the contact angle values of the coatings increased. The highest amount of fluorine containing coating showed a contact angle of 119 degrees. Then with the addition of nonfluorinatecl alkoxysilane compounds, a contact angle of 130 degrees was reached. Also the effect of post-cure temperature on contact angle values was investigated. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Polymers; AFM; Surface properties; Mechanical properties; SUPERHYDROPHOBIC SURFACES; RENEWABLE RESOURCE; POLYURETHANES; POLYOL